DIPENUHI DI DALAM KRISTUS PERSPEKTIF SURAT KOLOSE SEBAGAI LANDASAN BAGI GEREJA DALAM MELAYANI MASYARAKAT - Alberth Darwono Sarimin (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2020)
The existensi of the church in this world because of mandate mission of Jesus Christ. To know how the church can serve community well, in this paper the Colossians become a focus of research and the reason to choose this letter was the collosians consist of plural community.The purpose of this paper is to look at how religion sociology influences social life and theology can drive social change system. While the research method that was used is library researchSocial structure that is formed in Colossian community provides an opportunity for the growth of false teaching and seeing this social structure strongly built in Colossian Paul raised a theology of fullness of God in Christ and belivers are fulfilled in Christ. In other words that the supremacy of Christ in everything and over everythingThe existence of the church has a role to drive social system and to apply that system Christ should be supremed, supremacy of Christ is above the mission and the church has a strategy to carry out its mission. In other words, to be able to serve community, the church should place Christ over everything and have a strategy in carrying out its mission so that the church which is a sub system in the community able to move a larger system Keywords: Fulllness, fulfilled, supremacy, Christ